PELAKSANAAN FUNGSI PENGAWASAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP KINERJA EKSEKUTIF DI KOTA MEDAN - Jhonny Nadeak; Pendastaren Tarigan; Faisal Akbar Nasution; Agusmidah Agusmidah (USU LAW JOURNAL, 2014)
ABSTRACTLocal government system as the consequence of the democratric country that adheres to the deconcentration, decentralization and local autonomy principles goves the right to the local governments to significantly take care of their own domestic affairs as optimal as possible. The supervisory function of the members of regional legislative council was comprehensively regulated, but it was only limited to checks and balance without law enforcement authority. The implementation of the supervisory function of the members of regional legislative council against the peformance of the City Government of Medan in 2011 has not owned the ideal controlling system yet. The actions taken by the members of regional legislative council were merely in the forms of recommendation, criticism, suggestion and continuous monitoring.Keywords: upervision, Regional Legislative Council, Performance, City Government of Medan, Local Autonomy